Solution of Descriptor Lur'e Equations via Even Matrix Pencils. Issue 1 (December 2014) - Reis, Timo; Voigt, Matthias
Abstract Descriptor Lur'e equations are an important tool for the solution of linear‐quadratic optimal control problems for differential‐algebraic systems. In this article we discuss how one can construct all solutions of these equations by the deflating subspaces of associated even matrix pencils. (© 2014 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)